2017
DOI: 10.1002/spe.2551
|View full text |Cite
|
Sign up to set email alerts
|

K‐MING: A mobile proxy handoff control scheme for proximate group‐based geodata sharing

Abstract: This work adopts a mobile social network in proximity (MSNP)-centric group touring service concept to share geo-points of interest's (POIs') data among mobile users belonging to the same touring group. In a group-based touring service, a mobile user can create a group in the MSNP that can consist of some clusters in which some members having the 3G/3.5G/4G cellular network service are selected as cluster leaders to enable their Wi-Fi hot spot functions as mobile proxies. After that, each group member can join … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In our lab's previous work depicted in References 11, 12, it is found that it can achieve both (1) the reduction of (i) the downloaded data volume and the networking traffic in 4G/5G cellular network and (ii) the expense of using 4G/5G cellular network and (2) the reduction of power consumption at the same time in the 1‐level tree's sharing of downloaded POIs' contents using the multicasting transmission way for the image content, in which an adaptive Forward Error Correction technique was adopted to tackle the unreliable transmission issue in multicast. However, the group size, that is, the number of group members, of the 1‐level tree's proximate sharing is limited by the upper bound of the connected devices in the enabled Wi‐Fi AP of a handheld device.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our lab's previous work depicted in References 11, 12, it is found that it can achieve both (1) the reduction of (i) the downloaded data volume and the networking traffic in 4G/5G cellular network and (ii) the expense of using 4G/5G cellular network and (2) the reduction of power consumption at the same time in the 1‐level tree's sharing of downloaded POIs' contents using the multicasting transmission way for the image content, in which an adaptive Forward Error Correction technique was adopted to tackle the unreliable transmission issue in multicast. However, the group size, that is, the number of group members, of the 1‐level tree's proximate sharing is limited by the upper bound of the connected devices in the enabled Wi‐Fi AP of a handheld device.…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the service time of the group LBS scenario, the authors designed a method of having each group member's handheld device alternatively being the downloading handheld device to balance the power consumption among handheld devices. In Reference 12, in order to increase the size of the group, that is, increase the number of group members, the aforementioned scenario was extended to split group members' handheld devices into several clusters. Using the method proposed in Reference 12, each cluster head enables its Wi‐Fi AP's function to let its cluster members' handheld devices to connect, and then is in charge of downloading POIs' contents from the remote cloud server through the charged cellular network and forwarding the downloaded POIs' contents to its cluster members' handheld devices through the free Wi‐Fi network.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations